1966
DOI: 10.1901/jeab.1966.9-135
|View full text |Cite
|
Sign up to set email alerts
|

AUDITORY REACTION TIME AND THE DERIVATION OF EQUAL LOUDNESS CONTOURS FOR THE MONKEY1

Abstract: Monkeys were trained to release a telegraph key at the onset of a pure tone. Latency of the response was measured over a 70-db range of sound pressure (re 0.0002 dyn/cm(2)) at six frequencies (250 to 15,000 cps). Latency was found to be an inverse exponential function of intensity at all frequencies. Equal loudness was inferred from the equal latency contours which were constructed from the latency-intensity functions at each frequency. These data indicate peak auditory sensitivity for the monkey near 1000 cps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
0
3

Year Published

1981
1981
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(79 citation statements)
references
References 16 publications
7
69
0
3
Order By: Relevance
“…One might speculate that a greater latency effect would be observed under conditions of a more demanding task. That would be analogous to the observations from animal psychophysical studies showing longer reaction times for more demanding stimulus conditions (e.g., Stebbins, 1966;May et al, 2009).…”
Section: Spatial Sensitivity Varies With Anesthetic and Task Conditionssupporting
confidence: 83%
“…One might speculate that a greater latency effect would be observed under conditions of a more demanding task. That would be analogous to the observations from animal psychophysical studies showing longer reaction times for more demanding stimulus conditions (e.g., Stebbins, 1966;May et al, 2009).…”
Section: Spatial Sensitivity Varies With Anesthetic and Task Conditionssupporting
confidence: 83%
“…The approach was first applied to non-human primates in studies by Stebbins and colleagues (Miller et al 1969;Stebbins and Miller 1964), who characterized the relationship between RT and stimulus intensity (visual or auditory). These investigators reported equal latency contours that share many of the features of our present observations (Stebbins 1966), including a compressed range of latency/loudness measures at high frequencies (Fig. 7) and the extreme variation of RT near threshold (Fig.…”
Section: Previous Animal Psychophysical Studies Of Loudness Perceptionsupporting
confidence: 82%
“…The general consensus, therefore, seems to be that there is a close relationship between loudness and RT. Consequently, it has been proposed that RT may serve as an indirect estimate or surrogate for loudness and that RT measurements are a useful tool to investigate loudness perception (e.g., Chocholle 1940;Stebbins 1966;Reason 1972;Moody 1973Moody , 1979Pfingst et al 1975a;Dooling et al 1975;Marshall and Brandt 1980;Buus et al 1982;Humes and Ahlstrom 1984;Seitz and Rakerd 1997;Leibold and Werner 2002;Arieh and Marks 2003;Wagner et al 2004;Florentine et al 2005;Little and May 2005;see also Scharf 1978;Luce 1986). Snodgrass (1975, p. 37ff) has even suggested that RT may be used more generally as an index of the magnitude of a listener's sensation.…”
Section: Simple Rt and Loudnessmentioning
confidence: 99%
“…Simple RT to auditory stimuli is commonly thought to be a measure of the loudness of the reaction stimuli, and is consequently viewed as a useful tool to study loudness perception (e.g., Chocholle 1940;Stebbins 1966;Moody 1973Moody , 1979Pfingst et al 1975a;Dooling et al 1975;Marshall and Brandt 1980;Buus et al 1982;Humes and Ahlstrom 1984;Seitz and Rakerd 1997;Leibold and Werner 2002;Arieh and Marks 2003;Wagner et al 2004;Florentine et al 2005;Little and May 2005;see also Scharf 1978;Luce 1986). In this context, it has been observed that plots of the sound levels of tones of different frequencies that evoked identical and very long mean RTs yielded curves in close proximity to, and of similar shape as, the animal's audiogram (e.g., Pfingst et al 1975a;Dooling et al 1975), suggesting that iso-RT contours for very long mean RTs might reflect the audibility curve.…”
Section: Introductionmentioning
confidence: 99%